Implementation of the Australian Institute of Sport Female Performance and Health Initiative menstrual cycle education modules in elite Victorian Institute of Sport athletes - Lampard, S.; Crossley, K.; Donaldson, A.; Rio, E.; Hayman, M.; Mosler, A.; White, S.; Harris, R.; Bruder, A. (Journal of Science and Medicine in Sport, 2024)
Introduction: Female athletes and their support staff have limited knowledge of female-specific health considerations (e.g. the menstrual cycle) that might affect their health and performance. Given the importance of education in enhancing knowledge, the Australian Institute of Sport (AIS) established the Female Performance and Health Initiative (FPHI) in 2019 to support female athletes. The FPHI provides open access online educational modules to target education for female athletes, their coaches and performance support professionals. Modules include (i) The Normal Menstrual Cycle; (ii) Menstrual Abnormalities (1 and 2); (iii) Contraception for Female Athletes; and (iv) Coaching Considerations for Female Athletes (specifically for coaches of female athletes). The aim of this study was to evaluate the implementation of these modules among elite female athletes and their support staff. Methods: Victorian Institute of Sport (VIS) female athletes (=16-years) and support staff (e.g. coaches, performance support professionals, administrators) working directly with VIS female athletes were recruited to complete an online survey. The bespoke surveys were co-designed by the project team and piloted by VIS professionals working with VIS female athletes and elite female athletes. The Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) of the FPHI menstrual cycle and coaching modules were assessed based on the proprortion of VIS players and/or staff who: were aware of the modules (R), believed the modules changed their knowledge, belief, attitudes, confidence and/or behaviours (E), used the modules (A), shared or discussed the content with others (I), and used the modules multiple times (M). Descriptive statistics will be analysed using Stata. Results: 78 athletes (16-37 years, 20 sports) and 42 staff members (8 physiotherapists, 6 performance lifestyle advisors, 5 head coaches, 5 performance scientists, 5 strength and conditioning coaches, 4 nutritionists, 4 sports physicians, and 5 other) were recruited. About one-quarter (23.1%) of athletes and two-thirds (66.7%) of staff were aware (R) of at least one of the menstrual cycle modules. 7.7% of all athletes and 31.0% of all staff had completed at least one module (A). For athletes and staff combined, 41.3% of participants who were aware of the modules had completed at least one. Of participants who were not aware of the modules, 83% of athletes and 93% of staff wanted to know more about them. Effectiveness, implementation and maintenance was difficult to assess considering the low number of module use. Discussion: Most female athletes and their support staff in a state-based elite Australian sport environment were unaware of the FPHI menstrual cycle modules. However, there is an appetite to engage with these educational resources, with most participants wanting to know more about them. The lack of reach and adoption of the modules makes it challenging to assess the effectiveness, implementation, and maintenance in this population. Impact/Application to the field: